Is Land Degradation Neutrality feasible in dry areas?. (January 2015) - Grainger, Alan
Abstract: The aspirational goal of a land degradation neutral world, to be realized by reducing the rate of land degradation and increasing the rate of restoration of degraded land, was agreed at the Rio+20 Conference in 2012. This paper evaluates the feasibility of introducing a Land Degradation Neutral (LDN) scheme as an activity of the United Nations Convention to Combat Desertification (UNCCD). It concludes that national and international implementation would involve political, organizational and technological challenges. Monitoring restoration of desertified land by revegetation would be feasible immediately, but monitoring cuts in national rates of desertification would not, because no baseline rates are currently available; national and international scientific capacities to measure desertification are limited; and further scientific knowledge is required to supplement existing knowledge of desertification processes and of land use and land cover change processes generally. This paper therefore suggests introducing an LDN scheme in phases. Phase 1 would focus on restoring degraded lands, improving national land use planning systems, and establishing international and national monitoring capacities. Phase 2 would reduce desertification rates with the help of fully integrated land use planning and monitoring systems. Phase 3 would set a target year for realizing an LDN goal, based on experiences in Phases 1 and 2. All three phases would be informed by accessing existing scientific knowledge, and gaining new knowledge by launching a scientific LDN process that can evolve in parallel with the political process. Highlights: The Rio+20 Conference agreed a goal of a land-degradation-neutral world (LDN). The UN Convention to Combat Desertification (UNCCD) is still to adopt an LDN goal. This paper critically evaluates the feasibility of a UNCCD LDN scheme. It finds that an LDN scheme will face implementation and monitoring challenges. It also shows how science can help the UNCCD to meet these challenges.